O "outro" Nordeste: uma abordagem sobre a contribuição do olhar de Pierre Verger sobre o sertão - Menezes, Vanessa Alves (2013)
This study aims to make an interpretative reading of the tradition of the northeastern hinterlands through the eyes of French photographer Pierre Verger during his work for the magazine O Cruzeiro. We start from the perspective of the traveler-looking alien otherness and provides training ethnographic Verger. Within the national search for an identity, mainly Brazilian, touted by nationalist project since 1930, we demonstrate the involvement of a photojournalist for the construction of the idea of the Northeast and the identity of the people countryman between the years 40 and 50. Dipped in the intellectual and political context of the time and serving the media apparatus of the magazine O Cruzeiro, Verger embarks the borders of the Northeast casting his gaze abroad for many different cultural particularities that would compose the solidified image of |authentic Northeastern tradition|, marked by colonial and multicultural aspects. Thus, the image analysis is guided by the aesthetic Verger, noting cultural expressions revealed in human types, in daily work, religion and folk art.